2011
DOI: 10.1136/gut.2011.237412
|View full text |Cite
|
Sign up to set email alerts
|

Thiopurines prevent advanced colorectal neoplasia in patients with inflammatory bowel disease

Abstract: Thiopurine use protects IBD patients against the development of AN. The effect of 5-ASA appeared to be less pronounced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(78 citation statements)
references
References 35 publications
3
70
0
5
Order By: Relevance
“…These findings suggest that regular evaluation of disease activity, which may include surveillance colonoscopies and adjustment of medical interventions and eventually colectomy in intractable situations are the main protective factors in this patient population and not chemoprevention by 5-ASA therapy. This is supported by a study by Rutter et al [27], which implicated the severity of colonic inflammation and not the lack of 5-ASA therapy as the most important determinant of the risk of colorectal neoplasia, and by the fact that thiopurines, which have no known chemopreventive mechanisms, also lower the risk of CRC, probably by controlling intestinal inflammation [39,46]. Bernstein et al [41] even demonstrated a higher risk for CRC with longer duration of 5-ASA therapy, suggesting that perhaps not the 5-ASA therapy itself, but the sustained need for such a therapy due to not controlled symptoms, is a driving factor for the development of colonic neoplasia (table 3).…”
Section: -Asa and Chemopreventive Effects In Uc: Clinical Studiessupporting
confidence: 53%
See 2 more Smart Citations
“…These findings suggest that regular evaluation of disease activity, which may include surveillance colonoscopies and adjustment of medical interventions and eventually colectomy in intractable situations are the main protective factors in this patient population and not chemoprevention by 5-ASA therapy. This is supported by a study by Rutter et al [27], which implicated the severity of colonic inflammation and not the lack of 5-ASA therapy as the most important determinant of the risk of colorectal neoplasia, and by the fact that thiopurines, which have no known chemopreventive mechanisms, also lower the risk of CRC, probably by controlling intestinal inflammation [39,46]. Bernstein et al [41] even demonstrated a higher risk for CRC with longer duration of 5-ASA therapy, suggesting that perhaps not the 5-ASA therapy itself, but the sustained need for such a therapy due to not controlled symptoms, is a driving factor for the development of colonic neoplasia (table 3).…”
Section: -Asa and Chemopreventive Effects In Uc: Clinical Studiessupporting
confidence: 53%
“…The lack of a protective effect in the setting of dysplasia was attributed to the small sample size of only two studies comprising 96 cases. Ten more studies have been published since this meta-analysis [25,32,33,34,35,36,37,38,39,40,41]. Four of the studies were case control studies, one was a cohort study and five were population-based studies.…”
Section: -Asa and Chemopreventive Effects In Uc: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk for colorectal cancer increases with disease duration, anatomic extent of colitis and presence of other inflammatory disorders (such as primary sclerosing cholangitis), whereas it decreases when patients take drugs to reduce inflammation. Recently, two studies observed that thiopurine was associated with a decreased risk of colorectal cancer in the subgroup of IBD patients with longstanding extensive colitis [7,8]. …”
Section: Ibd and Cancermentioning
confidence: 99%
“…There was a protective effect of 5-ASA on CRC in UC patients, with an OR of 0.52 (95% CI: 0.29-0.95; p = 0.03), but this effect was not seen among CD patients (OR 0.62, 95% CI: 0.27-1.40; p = 0.25). Main studies that evaluated the relationship between 5-ASA treatment and CRC risk in IBD are summarized in table 1 [11,15,24,25,26,27,28,32,33,34,35,36,37,38,39,40,41,42,43,44]. …”
Section: -Asa and Chemoprevention: What Is The Current Level Of Evidmentioning
confidence: 99%